STUDY OF ACTIVITIES USING PDAM CLEAN WATER IN TAMALATE DISTRICT MAKASSAR CITY - Arie Satriadi Sadewa; Ratna Musa (Moeslim Indonesian University (UMI), 2018)
One of the most important urban infrastructure is clean water as well as basic human needs. Its use is not only limited to household needs but also for public, social and economic facilities. One way to obtain clean water is to use PDAM services. The Regional Drinking Water Company (PDAM) is a business entity that processes and serves the drinking water needs of the community. One of the problems that have and will arise in the management of clean water is that the ability of PDAMs as clean water providers is generally still limited both in terms of coverage and quality of service. This study aims to determine the economic and demographic characteristics of the population as well as the most dominant PDAM water use activity in households in Tamalate District. The desired quantity of water is to meet the standards of the needs of the metropolitan city. The desired continuity of flow is to meet 24 hours per day. The desired water quality is to meet the applicable standards of physical parameters. The results showed that based on field observations of the dominant economic characteristics, the highest activity was bathing, continuity and quality were still not effective because the quantity of water still did not meet all customer needs, continuity of flow still did not flow 24 hours per day for all customers, and still there are customers who complain about the quality of the clean water consumed in terms of turbidity, smell and taste.